The Impact of Covid-19 Pandemic on The Clinical Nutrition Interns Performances in King Abdulaziz Hospital- National Guard Health Affairs, Alahsa - Al-Shehri, Awad Mohammed; Al-Nasser, Sami; Khashwain, Seham; Al-Shehri, Abdullah (Journal of medical and pharmaceutical sciences, 2021)
COVID-19 has ruthlessly invaded the world causing a global disaster in many aspects and fields, particularly the field of medical and health education. Clinical Nutrition Internship Program, at KAMC-Al-Ahsa, has been affected by the precautionary measures in facing the pandemic of COVID-19. These measures may have their own impact on the performance of interns. Consequently, this study aims to determine the degree of such an impact of COVID-19 pandemic on interns’ performance, and also to explore any possible reasons behind it. Therefore, we have proposed our research objectives as follows: 1-mesuring the significance of the impact of COVID-19 on the clinical nutrition interns’ performances. 2- Identifying the reasons caused by COVID-19 that might explain any possible differences in the performance of clinical nutrition interns compared to the previous batch.Method: A t test was used for the comparison between the scores of all interns’ performance for two batches (during COVID-19 and the year before) as a causal comparative study by using the Clinical Nutrition Evaluation form to achieve our first objective. In addition, and to achieve the second objective, one to one interviews were conducted with all interns who have been doing their internship during COVID-19 to investigate and explore any challenges that might negatively influence their performance.Results: Our findings showed that there was a significant difference in the total mean scores of interns’ performance before and after COVID-19 (57.45 ± 1.761, 56.13 ± 1.058 respectively), with p-value 0.007 < 0.05, and a significant deference in Domain 1 (knowledge of work and working abilities) mean scores (27.75 ± 0.967, 26.43 ± 1.121 respectively) with p-value < 0.001 < 0.05 which means there was a significant impact on the clinical nutrition interns’ performances caused by COVID-19 compared to the year before. However, the differences in Domain 2 (Quality and quantity of work) and Domain 3 (General performance) were not significant. The one to one interviews were also conducted, and the data was prepared, organized, transcribed and reviewed by the research team. Coding then took place by labeling and organizing our data to categorize all emerged themes and understand the relationship between them. Coverage, communication, attention, belonging, stress and anxiety, teamwork and quality of work were the main themes that can explain the reasons behind the difference in interns’ performance before and during COVID-19.Recommendations: according the results, we recommend Increase the training hours in the hospital, the practical training and lowering theoretical training, facilitate the communication with the patients and other health professionals with lowering the physical contact, conduct more scientific meetings, workshops and seminars with the interns, provide more assignments and case scenarios for the interns to be done at home, provide additional courses for the interns to enhance their abilities in communication skills, stress management, time management and professionalism.
Keywords: COVID-19; Clinical Nutrition; Performance; Impact; Interns